Potential Of Bintaro (Carbera Odollam Gaertn) , Amethyst (Brugmansia Candida Pers) And Babandotan (Ageratum Conyzoides L) As A Biopesticide Against Pest Leptocorisa Acuta On Rice Plants - Wizni , Fadhillah; Rini, Susanti; Lisdayani (Talenta Publisher, 2020)
Abstract Rice plants (Oryza sativa) is a crop of the main food commodities in Indonesia. Rice production continues to be improved to meet the needs of the community, however, efforts to increase rice production still faces problems, namely Hama walang sangit Leptorisa acuta.. One alternative to control insect pests Leptorisa acuta relatively safe, inexpensive, and easily obtained is the utilization of botanical insecticides. One of them is by using plants Bintaro (Carbera odollam Gaertn), Amethyst (Brugmansia candida Pers) and Babandotan (Ageratum conyzoides L) vegetable insecticides. This study aimed to determine the effectiveness of Bintaro (Carbera odollam Gaertn), Amethyst (Brugmansia candida Pers) and Babandotan (Ageratum conyzoides L) in controlling the Pest Leptocorisa acuta. This study uses the RAL Non-Factorial with 6 Level of treatment and 5 replications. From the results obtained that the treatment with the use of plants kacubung can suppress the population of pest Leptocorisa cut by 100% by the time of application for 1 day after application. Of this study are expected in the future can use kacubung as insecticides with different pests so that in the future kacubung can be used as a vegetable insecticide that is environmentally friendly, economical, and right on target.